Visionary Leadership, Change and Organizational Culture of Madrasahs, and Direction of Educational Policy - Hadi, Nanda Aiyun Novyka; Muhammad, Muhammad; Agus, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This article discusses the importance of visionary leadership, organizational culture, and educational policy direction in creating quality education in madrasas. A visionary madrasa principal can inspire teachers, students, and educational staff, and encourage innovation and the use of technology in learning. Organizational culture shapes student character, strengthens madrasah identity, and maintains harmony among school members. Educational policy direction provides strategic guidance to ensure all educational programs align with national goals and empower human resources. The synergy of these three aspects creates a conducive, character-based, and competitive learning environment.